Pesan Dakwah dalam Film “Web Series Ustad Milenial” Karya Eko Kristianto - Mohamad Irham Sahari (Fakultas Agama Islam, Universitas Hasyim Asy'ari Tebuireng Jombang, 2024)
Preaching is not only done in mosques, prayer rooms, or in recitation events. But for the current era, films can also be used as a medium for preaching among the public. Film is a work of art produced by teamwork. Films require scenarios, actors, directors and other people who take part in the film production process, from cameraman, editor, lighting, art director, music arrangement to script writer. Da'wah media through art and culture can be more memorable in matters relating to the delivery of Islamic teachings. This can be a good opportunity for da'i to preach when the effects of the film can be filled with content that contains Islamic teachings. The formulation of the problem discussed in this thesis is what is the message of da'wah contained in the Ustad Millenial Web Series film. This study used qualitative research methods. The purpose of this study is to find the message of da'wah contained in the Web Series film Ustad Millenial. The data collection technique used is in the form of documentation. To answer the problem formulation described above, the researcher uses a qualitative approach using Charles Sanders Peirce's semiotic analysis model. As a result, researchers found several da'wah messages in the Millennial Ustad Web Series film, including: (1) The responsibility of a teacher to his students. (2) Muslims must always strive and pray to Allah SWT. (3) The obligation of a child to be filial to parents. (4) Prohibition of bribery in business. (5) The beauty and obligation of prayer for Muslims. (6) The firmness of the Muslim faith. (7) The law of interest in Islam. (8) Suggestions to say and answer greetings.